Managerial ownership profitability and firm value agency theory perspective - Listia Aulia Indy; Lia Uzliawati; Agus Sholikhan Yulianto (Institute of Computer Science (IOCS), 2023)
This study explains the phenomenon of the decline in the value of banking companies when the rupiah slumped in 2018. The purpose of this study was to reveal the effect of managerial ownership and profitability on firm value and the effect of managerial ownership on profitability. The population in this study is the banking sub-sector financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The results of the study show that managerial ownership has no effect on firm value and does affect profitability. Furthermore, profitability affects the firm value. This study shows the mediating role of profitability on the indirect effect of managerial ownership on firm value.